KOMUNIKASI NONVERBAL GURU PADA MURID TUNARUNGU DALAM MENINGKATKAN KEMAMPUAN BERINTERAKSI SOSIAL - Hasibuan, Inda Wardah; Ritonga, Syafruddin; Novri, Novri (PERSPEKTIF, 2020)
Communication is a basic social process in social life. In communication, we often find many obstacles in delivering the message. Especially delivering a message to a deaf people. Deaf people is a people who can?t hear because they have disturbance in hearing and usually they also can?t talk. There are 2 types of deaf people, deaf people that can?t hear totally and deaf people that can still hear a little. Special skill is needed for a teacher to teach them and can give them instruction and knowledge following the school?s curriculum. One of the technic is called Nonverbal Communication. The purpose of this study is for knowing the Nonverbal Communication technics that usually use by the teachers to teach the students to improve their ability to do social interaction in the state extraordinary primary school no 027701 located in te city of Binjai. The method used in this study is qualitative method usually explain the phenomena by collecting the data, and then analyse the data to get the conclusion. This study is done by direct observation and interviews that involving the teachers. And the result of this study, we can say that the role of the teachers in delivering the Nonverbal Communication is very important for the students ability to do interaction and communication.